Optimalisasi Pendapatan Asli Daerah (PAD) dalam Meningkatkan Pelayanan Publik - Kamala, Jum’iyatul; Selvi Aulya Salsa; Nurilawati; Wahjoe Pangestoeti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine in depth the strategic role of Regional Own-Source Revenue (PAD) in improving the quality of public services as a manifestation of regional autonomy and fiscal decentralization in Indonesia. Amid challenges such as fiscal inequality and dependency on central government transfers, optimizing PAD is crucial to achieving financially independent regions capable of delivering high-quality public services. Using a descriptive qualitative approach and literature review of various sources, including local government budgets (APBD) and regional financial reports, the study finds that successful PAD optimization strategies involve intensifying and expanding revenue sources, enhancing the capacity of human resources, and strengthening transparent and participatory public financial governance. The finding indicate that regions with effective PAD management tend to have better and more sustainable public service deliver.